Asymptomatic subjects with airway obstruction have significant impairment at exercise - Soumagne, Thibaud; Laveneziana, Pierantonio; Veil-Picard, Matthieu; Guillien, Alicia; Claudé, Frédéric; Puyraveau, Marc; Annesi-Maesano, Isabella; Roche, Nicolas; Dalphin, Jean-Charles; Degano, Bruno (Thorax, 2016)
BackgroundThe relevance of screening for airway obstruction in subjects not complaining of COPD symptoms may depend on the definition of airway obstruction. Response to exercise in asymptomatic subjects with persistent airway obstruction as defined by a postbronchodilator FEV1/FVC <5th centile lower limit of normal (LLN) remains unknown.MethodsDyspnoea (Borg scale), exercise tolerance and ventilatory constraints on tidal volume expansion were assessed in 20 consecutive asymptomatic subjects with persistent mild airway obstruction detected by screening (postbronchodilator FEV1/FVC z-score: −2.14±0.29; FEV1 z-score: −1.02±0.64) undergoing incremental cycle cardiopulmonary exercise testing, compared with 20 healthy controls with normal spirometry matched for age, sex, body mass index and smoking history (FEV1/FVC z-score: −0.13±0.57; FEV1 z-score: 0.32±0.67) and with 20 symptomatic patients with COPD matched for the same characteristics (FEV1/FVC z-score: −2.36±0.51; FEV1 z-score: −1.02±0.48).ResultsAsymptomatic subjects with airway obstruction had higher dyspnoea ratings than controls during incremental exercise. Asymptomatic subjects with airway obstruction had also peak oxygen consumption and peak power output that were lower than controls, and similar to those observed in patients with COPD. Although less frequent than in COPD, dynamic hyperinflation was more frequent in asymptomatic subjects with airway obstruction than in controls (85%, 50% and 10%, respectively; p=0.01 in asymptomatic subjects vs controls and p=0.04 vs COPD).ConclusionsAlthough they did not present with chronic activity-related dyspnoea, subjects with a postbronchodilator FEV1/FVC<LLN as detected by screening had poorer exercise tolerance than healthy controls on exertion, and a significant proportion of them had dynamic hyperinflation. These subjects may, therefore, deserve further attention and may warrant regular follow-up.